Cell Biology - Karp, Gerald (John Wiley & Sons, 2014)
Written for an introductory course in cell and molecular biology, this text elaborates on fundamental concepts, such as the relationship between molecular structure and function, the use of chemical energy in operating cellular activities, and the observed unity and diversity at macromolecular and cellular levels.